Understanding demand for broken rice and its potential food security implications in Colombia - Phillips, Juliann; Durand-Morat, Alvaro; Nalley, Lawton L.; Graterol Matute, Eduardo Jose; Bonatti, Michelle; Loaiza de la Pava, Katerine; Urioste, Sergio; Yang, Wei (Elsevier, 2024)
Rice is a crucial contributor to global food security and is an important staple for over half the world's population. Irrigated paddy rice is a water-intensive crop, and an important contributor to greenhouse gas emissions. Thus, improving the efficiency of using rice as food rather than non-food uses is paramount to sustainably feeding a growing global population. One source of inefficiency in the rice market is using broken rice for non-food purposes. This study focuses on consumer preferences for rice with different broken percentages in Colombia. We used a mixed-method approach to ascertain the stated (experimental setting) and revealed (using samples that consumers independently purchased in a market) willingness to pay for broken rice to assess whether the rice market in Colombia efficiently prices rice quality. The findings highlight that consumers are aware of quality differences and are willing to pay a premium for rice with a low broken percentage, but also point to potential inefficiencies given that the willingness to pay estimates from both the two methods are statistically different. We find that the discount revealed in the market is significantly higher than that stated experimentally, which can have implications for pricing rice based on quality. Both methods found consumers were willing to pay a premium for rice under 10% broken, but beyond that threshold, there were no differences in willingness to pay. The Colombian rice industry and policymakers can use these findings to make the domestic rice market more responsive to the revealed preferences of consumers, which could have significant consequences for food security and sustainability.